Parotid sparing in RapidPlan Oropharynx models: To split or not to split. Issue 1 (11th February 2020) - O'Toole, James; Wu, Kenny; Bromley, Regina; Stevens, Mark; Eade, Thomas; van Gysen, Kirsten; Atyeo, John
Abstract: Introduction: Differences in knowledge and experience, patient anatomy and tumour location and manipulation of inverse planning objectives and priorities will lead to a variability in the quality of radiation planning. The aim of this study was to investigate whether parotid glands should be treated as separate or combined structures when using knowledge‐based planning (KBP) to create oropharyngeal plans, based on the dose they receive. Method: Two separate RapidPlan (RP) models were created using the same 70 radical oropharyngeal patients. The 'separated model' divided the parotids into ipsilateral and contralateral structures. The 'combined model' did not separate the parotids. The models were independently validated using 20 patients not included in the models. The same dose constraints and priorities were applied to planning target volumes (PTVs) and organs at risk (OARs) for all plans. An auto‐generated line objective and priority was applied in both models, with parotid mean dose and V50 doses evaluated and compared. Results: Plans optimised using the combined model resulted in lower ipsilateral mean doses and lower V50 doses in 80% and 75% of cases, respectively. Fifty‐five per cent of plans produced lower mean doses for the contralateral parotid when optimised using the combined model, while lower V50 doses were evenly split between the models. Conclusion: Combining the data for both parotids into one RP model resulted in better ipsilateral parotid sparing. Results also suggest that a combined parotid model will spare dose to the contralateral parotid; however, further investigation is required to confirm these results. Abstract : Differences in knowledge and experience, patient anatomy and tumour location and manipulation of inverse planning objectives and priorities will lead to a variability in the quality of radiation planning. The aim of this study was to investigate whether parotid glands should be treated as separate or combined structures when using knowledge based planning (KBP) to create oropharyngeal plans. Combining the data for both parotids into one RP library resulted in better ipsilateral parotid sparing. Results also suggest that a combined parotid library will spare dose to the contralateral parotid, however further investigation is required to confirm these results.